If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10a + 3(8 + 8r) = 24 + r -10a + (8 * 3 + 8r * 3) = 24 + r -10a + (24 + 24r) = 24 + r Reorder the terms: 24 + -10a + 24r = 24 + r Add '-24' to each side of the equation. 24 + -10a + -24 + 24r = 24 + -24 + r Reorder the terms: 24 + -24 + -10a + 24r = 24 + -24 + r Combine like terms: 24 + -24 = 0 0 + -10a + 24r = 24 + -24 + r -10a + 24r = 24 + -24 + r Combine like terms: 24 + -24 = 0 -10a + 24r = 0 + r -10a + 24r = r Solving -10a + 24r = r Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-24r' to each side of the equation. -10a + 24r + -24r = r + -24r Combine like terms: 24r + -24r = 0 -10a + 0 = r + -24r -10a = r + -24r Combine like terms: r + -24r = -23r -10a = -23r Divide each side by '-10'. a = 2.3r Simplifying a = 2.3r
| .2x+3.5=16.1 | | 2(2x-1)=26 | | 0.25y-0.01x=0.005 | | y=12-9 | | 6(3.14)=w-6(3.14) | | ((x-1)/3)-2=((x-5)/4) | | 2x+18y=18 | | 3x-11=2x+33 | | 14-b=8 | | -4+3x=7x+x+14x-8x | | 65=-6-x | | 81=x+181 | | 6/10-2/100 | | V-10=-19 | | -4+3x=7x+x+14-8x | | 9a-6=8a+1 | | 2x+2x+x+3x+3=24 | | 2x+0=5y-0 | | 5x+6=9x+3+8x | | 7bf^4-7bk^4= | | 6u(-5u^4)=0 | | 2a-1=3(a+1)+7a+5 | | X+4+5x+3+4x=21 | | (y^-1/4)^1/6 | | 9-3v=0 | | 17x-36=12x+7 | | x+8=-72 | | 2(x-6)=3(x-4) | | y^(3/2)-10y | | 18=x/7 | | 66=1.5x | | -5(6y-6)-y=-3y(y-5) |